Virulence adaptation in a rice leafhopper: Exposure to ineffective genes compromises pyramided resistance. (November 2018) - Horgan, Finbarr G.; Bernal, Carmencita C.; Vu, Quynh; Almazan, Maria Liberty P.; Ramal, Angelee Fame; Yasui, Hideshi; Fujita, Daisuke
Abstract: Pyramiding resistance genes is predicted to increase the durability of resistant rice varieties against phloem-feeding herbivores. We examined responses by the green leafhopper, Nephotettix virescens (Hemiptera: Cicadellidae), to near-isogenic rice lines with zero, one and two resistance genes. The recurrent parent (T65) and monogenic lines ( GRH2- NIL and GRH4- NIL) with genes for resistance to the green rice leafhopper, Nephotettix cincticeps (Hemiptera: Cicadellidae), were susceptible to the green leafhopper, but the pyramided line ( GRH2/GRH4- PYL) was highly resistant to the green leafhopper. We selected green leafhoppers, N. virescens, from five sites in the Philippines for over 20 generations on each of the four lines. Populations selected on GRH2/GRH4- PYL gained partial virulence (feeding and development equal to that on T65) to the pyramided line within 10 generations and complete virulence (egg-laying equal to that on T65) within 20 generations. After 20 generations of rearing on the susceptible monogenic lines, green leafhoppers were also capable of developing and laying eggs on GRH2/GRH4- PYL. Furthermore, green leafhoppers reared on the susceptible GRH4- NIL for 20 generations showed equal preferences for T65 and GRH2/GRH4- PYL in choice bioassays. Our results indicate that previous long-term exposure to ineffective genes (including unperceived resistance genes) could dramatically reduce the durability of pyramided resistance. We suggest that informed crop management and deployment strategies should be developed to accompany rice lines with pyramided resistance and avoid the build-up of virulent herbivore populations. Highlights: Monogenic rice lines with GRH2 and GRH4 loci were susceptible to green leafhopper. A pyramided line with both genes was highly resistant to the leafhopper. Populations selected for 20 generations adapted to feed and oviposit on the pyramided line.